Programa de mentoría en la retención y éxito académico de estudiantes de ciencias sociales de la Facultad de Ciencias de la Educación y Humanidades de la Universidad Nacional de la Amazonía Peruana 2023 - Zambrano Curitima, Jhosiveth Jheninfer (2025)
The study evaluated the impact of a mentoring program on the retention and academic success of CC. SS. students at the FCEH-UNAP, Iquitos, during 2024, using a quasi-experimental design with an experimental group (GE=25) and a control group (GC=24). Variables such as retention, academic performance, participation in extracurricular activities and student satisfaction were analyzed. The pre-test showed low levels of satisfaction in both groups, justifying the intervention. After mentoring, the post-test showed significant improvements in all the dimensions evaluated, with statistically significant results according to the Shapiro-Wilk and Mann-Whitney U test, confirming that mentoring is an effective strategy to reduce dropout and improve student performance, thus validating the research hypothesis.